Character Education and the Role of the Bau Nyale Festival in the Myth of Princess Mandalika as an Effort to Preserve the Traditions and Culture of the Sasak Tribe Lombok - Sofiyan, Adrian Ali; Raharjo, Resdianto Permata (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
This research attempts to describe character education alongside the strategic role of the Bau Nyale Festival in preserving the traditions and culture of the Sasak people on Lombok Island. In the midst of globalization which introduces a rationalistic and materialistic mindset, this festival is seen as an important means of maintaining local wisdom, ensuring that culture is not eroded by foreign culture, and ensuring that noble values ​​are passed on to the younger generation. In addition, this study tries to explore how this tradition supports the resilience of the regional tourism sector based on culture. The method applied in this research is a qualitative approach using ethnographic methods. Data collection was carried out through direct observation at the location, precisely in Kuta Village (Kuta Beach/Seger), Pujut District, Central Lombok Regency. Apart from observations, researchers conducted in-depth interviews with traditional leaders and local residents, and documented various cultural activities that took place during the festival. The data is then analyzed comprehensively with the aim of interpreting events and cultural elements that develop in that society. Research findings show that the Bau Nyale Festival is a combination of respecting the historical myth of Princess Mandalika and strengthening the ethnic identity of the Sasak people. The moral education values ​​found include willingness to sacrifice, spirit of mutual cooperation, and sportsmanship. Various activities supporting the festival, such as the Peresean tradition and traditional Gendang Beleq music, have proven effective in instilling character values ​​such as courage, resilience, discipline, responsibility and teamwork in the younger generation. Therefore, this festival functions as an educational instrument as well as a behavioral "compass" that aligns the life of modern society with the social order and ancestral heritage.